A safe and reusable imaging chamber compatible with organic solvents. (25th April 2020) - Colombini, Martin; Pasierbek, Pawel; Masselink, Wouter
Abstract: High refractive index organic solvents are commonly used as an imaging medium in tissue clearing approaches. While effective, such solvents provide serious concerns for the safety of users and the equipment, especially in a central microscopy unit. To overcome these concerns, we have developed a large and reusable imaging chamber compatible with the universal mounting frame AK (PeCon GmbH). This chamber is easy to assemble and significantly improves the working environment in a central microscopy unit, where hazardous chemicals could negatively affect equipment and people. To encourage the uptake of these chambers, the design is made publicly available for download.